2004
DOI: 10.1097/01.alc.0000117835.49673.cf
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ethanol Administration and Induction of Anxiety‐Related Affective States on the Acoustic Startle Reflex in Sons of Alcohol‐Dependent Fathers

Abstract: The acoustic startle reflex seems to be reduced in sons of alcoholics. The nonsignificant results during startle modification do not support the concept of increased reactivity to anxiety-related environmental stimuli as a mechanism promoting alcohol use disorders in subjects at increased family genetic risk for alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…In relation to genetic association studies in humans, the current findings in mice selectively bred for high or low alcohol preference are in contrast to results of one study that found no differences in FPS in people with a positive versus a negative family history of alcoholism (Zimmermann et al, 2004). However, the present data are generally supportive of other findings in humans where an increased prevalence of comorbid alcoholism and anxiety disorders has been reported in relatives of people with alcoholism and/or anxiety disorders (Merikangas et al, 1994.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In relation to genetic association studies in humans, the current findings in mice selectively bred for high or low alcohol preference are in contrast to results of one study that found no differences in FPS in people with a positive versus a negative family history of alcoholism (Zimmermann et al, 2004). However, the present data are generally supportive of other findings in humans where an increased prevalence of comorbid alcoholism and anxiety disorders has been reported in relatives of people with alcoholism and/or anxiety disorders (Merikangas et al, 1994.…”
Section: Discussionsupporting
confidence: 78%
“…Grillon et al (1998) reported that adolescents with a positive family history of anxiety disorders showed greater FPS relative to family history-negative individuals. Zimmermann et al (2004) found no differences in FPS in subjects who differed in genetic risk for alcoholism (positive vs negative family history). However, in selectively bred rats that differ in genetic propensity toward alcohol drinking, alcohol-preferring (P) rats showed greater FPS than the alcohol-nonpreferring (NP) line (McKinzie et al, 2000).…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover, a significant association between startle magnitude after alcohol consumption and the frequency of drinking alcohol has been shown [70]. The acoustic startle reflex also seems to be reduced in sons of alcoholics, independently of comorbid anxious disorders [179]. A recent study [94] showed that although drinking behaviour and craving decreased significantly over time, the pattern of the affective modulation of the startle reflex did not change.…”
Section: The Startle Responsementioning
confidence: 98%
“…For example, adult sons of alcoholics (SOAs) display increased heart rates and greater vein constriction (classic cardiovascular stress responses) preceding an unavoidable electric shock compared to controls (Finn, Zeutouni, & Pihl, 1990), and adolescent SOAs display increased heart rates compared to non-SOAs while performing a mental arithmetic task (psychological stressor; Harden & Pihl, 1995). On the other hand, one study reported similar acoustic startle in response to threat of electric shock in SOAs compared to controls (Zimmermann, Spring, Wittchen, & Holsboer, 2004) and another study showed reduced skin conductance responses in anticipation of electric shock compared to controls (Finn, Kessler, & Hussong, 1994). These results may suggest that SOAs are more reactive to stressful stimuli under certain experimental conditions; however, more study is needed to clarify the basis of contradictory results.…”
Section: Introductionmentioning
confidence: 99%